Exploring astro-tourism and education in Kenya and Tanzania: A literature review - Mkwizu, Kezia H.; Kimeto, Janet C. (School of Tourism, Universitas Ciputra Surabaya, 2024)
Past scholars noted that one of the challenges is education in relation to tourism particularly the aspects of training and curriculum design. Existing literature has explored challenges of customer services education in tourism and suggest measures such as retraining and improving the curricula as a remedy to match the skills needed in the post pandemic for the hospitality and tourism industry. Conversely, there is less attention on other forms of tourism like astro-tourism. Hence, this paper’s aim is to expand literature on education in tourism with the main objective of exploring astro-tourism and education in tourism. Guided by the behaviorist learning theory, the specific objective is to explore the forms of astro-tourism and training programs from the perspective of Kenya and Tanzania. A systematic literature review supplemented by integrative literature review is deployed as a research methodology. A total of 16 papers from journals, conferences and newsflash deemed sufficient for descriptive statistics and literature analysis to avail findings. The findings indicate that although various forms of astro-tourism exist, these are not fully complemented with training programs. Very few public institutions or private enterprises offer astro-tourism programs like astro tour guide. The findings suggest that both higher education institutions and the private sector should continue promoting tourism education that includes training programs aligned with the growing trends in astro-tourism.